Low-level Cxcr4-haploinsufficient HSC engraftment is sufficient to correct leukopenia in WHIM syndrome mice - Gao, Ji-Liang (JCI Insight, 2019)
Warts, hypogammaglobulinemia, infections, and myelokathexis (WHIM) syndrome immunodeficiency is caused by autosomal dominant gain-of-function mutations in chemokine receptor CXCR4. Patient WHIM-09 was spontaneously cured by chromothriptic deletion of 1 copy of 164 genes, including the CXCR4(WHIM) allele, presumably in a single hematopoietic stem cell (HSC) that repopulated HSCs and the myeloid lineage. Testing the specific contribution of CXCR4 hemizygosity to her cure, we previously demonstrated enhanced engraftment of Cxcr4(+/o) HSCs after transplantation in WHIM (Cxcr4(+/w)) model mice, but the potency was not quantitated. We now report graded-dose competitive transplantation experiments using lethally irradiated Cxcr4(+/+) recipients in which mixed BM cells containing approximately 5 Cxcr4(+/o) HSCs and a 100-fold excess of Cxcr4(+/w) HSCs achieved durable 50% Cxcr4(+/o) myeloid and B cell chimerism in blood and approximately 20% Cxcr4(+/o) HSC chimerism in BM. In Cxcr4(+/o)/Cxcr4(+/w) parabiotic mice, we observed 80%–100% Cxcr4(+/o) myeloid and lymphoid chimerism in the blood and 15% Cxcr4(+/o) HSC chimerism in BM from the Cxcr4(+/w) parabiont, which was durable after separation from the Cxcr4(+/o) parabiont. Thus, CXCR4 haploinsufficiency likely significantly contributed to the selective repopulation of HSCs and the myeloid lineage from a single chromothriptic HSC in WHIM-09. Moreover, the results suggest that WHIM allele silencing of patient HSCs is a viable gene therapy strategy.